The Stress Analysis in Pulleys and Blocks - Aliyeva, S.Y.; Kerimova, I.M. (Herald of Azerbaijan Engineering Academy, 2023)
The article studies a three-dimensional finite element analysis of voltages in pulleys and describes the developed preprocessor for obtaining data for pulleys of various configurations. A model is constructed that takes into account the features of pulleys due to geometry and loads on the basis of eight nodal and twelve nodal isoparametric elements. When generating geometric data, the preprocessor needs twenty punch cards to produce a mesh of any of the seven types of pulleys selected for testing in the test lab. For a particular pulley under load, a very good agreement between the numerical and experimental results on deformations was obtained.